Slow Food Terra Madre: A Novel Pathway to Achieving Indigenous Australian Food Sovereignty? - Zuzanna Kruk-Buchowska (Anglica. An International Journal of English Studies)
The aim of this paper is to analyse the participation of Indigenous Australians in Slow Food International’s 2018 Salone del Gusto-Terra Madre meeting in Turin, Italy. Slow Food is a global grassroots organisation created to promote local food cultures and traditions, and the organisation’s Terra Madre network highlights the urgent need to protect the food-production systems of Indigenous peoples, valuing their holistic approach and recognising them as custodians of biodiversity. By creating a platform for Indigenous peoples to meet and discuss their challenges and ideas, and by putting Indigenous knowledges and stewardship of the environment at the centre of discussions about tackling global environmental challenges, the organisation encourages its Indigenous members to work toward food sovereignty in their respective countries as well as on an international level.